Efektivitas Guru PAK Dalam Meningkatkan Prestasi Belajar Siswa - Filemon Filemon (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
Effective learning is one of the important things for students. Therefore, teachers must be effective in teaching. Teacher effectiveness is the effectiveness that brings the success of students in participating in the learning process. PAK teacher effectiveness is a way to strengthen students' faith and improve student learning achievement. The way to find out effectiveness must be an evaluation, so that you understand the effectiveness of PAK teachers in learning. However, there are factors that affect student learning achievement, namely psychological factors. Thus, as an PAK teacher, he must be able to have effectiveness in learning to improve student learning achievement